Odwołania do Ojców Kościoła i pisarzy kościelnych okresu patrystycznego w kazaniach biskupa Pawła Kubickiego - Warso, Albert (Vox Patrum, 2025)
Bishop Pawel Kubicki (1871-1944) is best known for his writing as well as for his pastoral activities. During his priestly and episcopal ministry, he preached many sermons. Some of them have been printed. This article aims to identify and discuss references to the Church Fathers and ecclesiastical writers of the patristic period in his preaching activity. These references appear in his main preaching work, which is the collection Żywe słowo na ambonie i poza amboną. This publication is therefore the main source of the present study. It contains a selection of the sermons he preached during almost his entire life, and was published seven years before the author’s death. Out of up to three volumes planned by him, only the first volume was published. Bishop P. Kubicki referred most often to the ideas of St Augustine, as well as to the events in his life.